Vegetation of silicicolous grasslands of the highlands of North-Eastern Slovenia - Škornik, Sonja (Hacquetia, 2006)
Vegetation of the silicicolous grasslands of the highlands of North-Eastern Slovenia has been sampled with standard Braun-Blanquet procedure. All the 102 collected releves have been classified within the order Nardetalia Oberd. ex Preising 1949. The association Homogyno alpinae-Nardetum Mráz 1956 (all. Nardo-Agrostion tenuis Sillinger 1933) has been stated, inside which the typical form and the transitional forms to the heaths with Ericaceae have been distinguished. Chorology, life forms and spontaneous reforestation are discussed and nature-conservancy issue is mentioned.
Keywords: botanika; fitocenologija; phytosociology; Rhododendron-Park Bremen; silikatna travišča; Slovenia; Slovenija